Analysis on the torque characteristics due to outer rotor displacement in the double rotor switched reluctance machine - Aravind, C. V.; Misron, Norhisam; Raja Othman, Raja Nor Firdaus Kashfi; Aris, Ishak; Marhaban, Mohammad Hamiruce; Nirei, Masami (2013)
The paper presents the influence on torque characteristics of the outer rotor displacement in the double rotor reluctance motor. At the first stage the magnetic equivalent circuit of the machine is developed based on the magnetic circuit of the machine in each of the parts that describes their own reluctances. From the equivalent circuit at the particular position the net reluctance is calculated. The magnetic circuit reluctances include due to the iron core of the stator, the rotor and that of the air gaps. The air gap reluctance in different rotor position influences predominantly the torque characteristics as the torque development highly dependent upon the flux linkages at any position. The changing of the pole arc essentially improves the extended flux linkage capability. Hence an investigation into the variations on the displacement of the rotor pole is imperative. In this investigation attempt is made only on the displacement of the outer rotor pole with respect to that of the inner rotor pole. From the results it is inferred that displacing the outer rotor by 3 degrees evolves an improvement in the torque characteristics.